Evidence-based guidance for community management of lower limb haematomas in the absence of national standards - Christina Hayward (British Journal of Community Nursing, 2026)
Haematoma management in community settings presents a clinical challenge because of the absence of standardised national guidance. Haematomas, defined as localised collections of clotted or partially clotted blood within tissues, can result in complications such as skin necrosis, infection and delayed healing if not managed appropriately. This article outlines the assessment and management of closed, open-bleeding and open-clotted haematomas, with emphasis on timely escalation and risk identification, based on the haematoma clinical decision guide designed by the author to address hesitation and poor confidence among nurses in dealing with haematomas in the community. The importance of holistic assessment is highlighted, including comorbidities, coagulation status and recognition of complications such as compartment syndrome. Particular consideration is given to lower limb haematomas, where vascular assessment is essential before initiating compression therapy. Appropriate debridement options for community practice such as autolytic, mechanical and biological are discussed. This approach aims to improve clinical decision making and optimise patient outcomes.